Apontamentos sobre as categorias rural, urbano, campo, cidade: a perspectiva de um continuum - Rosa, Lucelina Rosseti (2017)
This article objective contribute for debate about the problematic ruralurban, develop in last years, in yours measurements theoretical and practical. Checking as the categorvs countryside, city, rural, urban have been labouriou from brazilians academics, in differents disciplines, the reflection is as starting the recent debate about the production ol statistics about the spaces countryside and dry, and rescue studyies representatives in the deeades of sixty, seventy and eighty that: approach the features socials anil cultural of the relation countryside-city. The effort in the reflection is to organize is as was method lhes debates theoretical, consider the notion of continuum; in the second place, to call attract attention for the use of categorys (empiridy), and for importance talk over this problematical in level municipal.